Edukacja wielokulturowa wczoraj, międzykulturowa dziś, transkulturowa jutro = Multicultural education yesterday, intercultural education today, transcultural education tomorrow - Niewiński, Jakub (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is an attempt to explain the meaning of the following terms: multiculturalism, interculturalism, transculturality in the context of the development of axiological competences by young people. The author shares his extensive experience in the implementation of local and international educational projects as part of the School of Dialogue - a program, thanks to which students from Murowana Goślina discovered the Jewish past of their town and developed their own tolerance. The article refers to the concept of ten principles of dialogue, the implementation of which is an opportunity to strengthen attitudes among students of the Polish school based on respect for otherness and acceptance of diversity
Keywords: wielokulturowość; międzykulturowość; transkulturowość; kompetencje aksjologiczne; komunikacja; dialog; szkoła dialogu; tożsamość; Żydzi; multiculturalism; interculturalism; transculturalism; axiological competences; communication; dialogue; school of dialogue; identity; Jews